Physicochemical Characteristics of Biscuits With the Fortification of Asian Swamp Eel Flour - Wulandari Wulandari; Herpandi Herpandi; Shanti Dwita Lestari; Rizky Maharani Putri (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Biscuits are light food to resist starving. This study was aimed to determine the physicochemical characteristics of the biscuits fortified with Asian swamp eel flour at several different concentration levels. Research design of this study Completely Randomized Design (CRD) with fortification of Asian swamp eel flour were 10; 20; 30; 40 and 50%. Testing parameters were color (lightness, hue and chroma), chemical content, calcium and phosphorus content. Treatments of 10-50% Asian swamp eel flour fortification on biscuit had significant effect (p<0.05) on ash content, protein, carbohydrate, calcium, phosphorus, and color (lightness and hue), but did not have significant effect (p>0.05 ) on moisture content, fat and chroma value. Asian swamp eel biscuits have higher levels of protein, moisture, ash and lipid than indonesian national quality standards of biscuits. The best treatment was 30% Asian swamp eel flour fortification with the chemical composition: moisture content 5.58±0.40% (w/w), ash 2.56±0.19% (w/w), lipid 30.72±4.02% (w/w), protein 15.89±0.55% (w/w) and carbohydrates 46.92±2.04% (w/w) while calcium and phosphorus content 0.40±0.00% and 0.58±0.01%, respectively.